Chronic disease self-management within the monthly benefit cycle of the Supplemental Nutrition Assistance Program. Issue 12 (August 2019) - Kinsey, Eliza Whiteman; Dupuis, Roxanne; Oberle, Megan; Cannuscio, Carolyn C; Hillier, Amy
Abstract: Objective: The present study explored chronic disease management over the monthly benefit cycle among primary food shoppers from households receiving Supplemental Nutrition Assistance Program (SNAP) benefits in Philadelphia, PA, USA. Design: In-depth interviews, participant observation and surveys were conducted with the primary food shopper of SNAP households. Setting: Interviews and surveys were conducted in a clinical setting at Children's Hospital of Philadelphia, at participants' homes, and in food procurement settings including grocery stores, food pantries and soup kitchens. Participants: Eighteen adults who received SNAP; five with a diet-related chronic condition, five managing the chronic condition of a family member and thirteen with overweight or obesity. Results: All households had at least one member with a chronic disease or condition. Households reported that the dietary demands of managing chronic illnesses were expensive and mentally taxing. Food and financial shortfalls at the end of the benefit cycle, as well as reliance on charitable food assistance programmes, often had negative impacts on chronic disease self-management. Conclusions: Drawing from nearly 50 h of in-depth qualitative interviews with SNAP participants, the study highlights the dual cognitive burden of poverty and chronic disease and elucidates the particular challenges of food procurement and maintenance of diet quality throughout the benefit month faced by SNAP households with diet-related chronic diseases. Interventions targeted at reducing the cost of medically appropriate, healthy foods may help to improve chronic disease self-management within SNAP populations.